Parler femme, parler hégélien: Applying Irigaray’s Mimesis Technique to Hegel’s Philosophy of Nature (Revista Eletrônica Estudos Hegelianos, 2022)
This text is an attempt to implement a feminist reading of Hegelian philosophy. In particular, the activity of mimesis proposed by Luce Irigaray, one of the greatest exponents of feminism of sexual difference, is applied to the Hegelian philosophy of nature. To implement this practice, several steps are necessary. Firstly, to develop an ontological explanation of nature capable of demonstrating the constitutively ‘excessive’ character of nature in relation to the concept, which maintains a fidelity to Hegelian thought and retains the speculative character of the relationship between Idea and nature. Secondly, to analyse Irigaray’s concept of mimesis, consisting in that ‘conscious masquerade’ through which it is possible to unhinge the ‘phallocentric’ order from within, thus opening the space for a symbolic order for woman as a subject Other. Finally, to interrogate the symbolic link posed by Hegel – as well as by western culture in general – between woman and nature, in order to apply the exercise of mimesis to the Hegelian philosophy of nature. Indeed, if nature is symbolically linked to woman then, given the ontological explanation of nature presented here, the possibility of a symbolic reading of Hegel arises which gives space for an essence different to that of the concept to appear.